1995
DOI: 10.1017/s0022112095002813
|View full text |Cite
|
Sign up to set email alerts
|

A fully nonlinear Boussinesq model for surface waves. Part 1. Highly nonlinear unsteady waves

Abstract: Fully nonlinear extensions of Boussinesq equations are derived to simulate surface wave propagation in coastal regions. By using the velocity at a certain depth as a dependent variable (Nwogu 1993), the resulting equations have significantly improved linear dispersion properties in intermediate water depths when compared to standard Boussinesq approximations. Since no assumption of small nonlinearity is made, the equations can be applied to simulate strong wave interactions prior to wave breaking. A high-order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
616
1
13

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 825 publications
(652 citation statements)
references
References 5 publications
22
616
1
13
Order By: Relevance
“…These equations are numerically implemented using a finitedifference algorithm and an iterative, high-order predictor-corrector scheme (Wei et al, 1995;. The open-ocean boundaries accommodate radiation of wave energy through a sponge layer, whereas runup on land boundaries is accommodated using a moving-boundary algorithm .…”
Section: Hydrodynamic Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…These equations are numerically implemented using a finitedifference algorithm and an iterative, high-order predictor-corrector scheme (Wei et al, 1995;. The open-ocean boundaries accommodate radiation of wave energy through a sponge layer, whereas runup on land boundaries is accommodated using a moving-boundary algorithm .…”
Section: Hydrodynamic Modelingmentioning
confidence: 99%
“…2. In general, linear models that explicitly include slope, through a mild slope approximation for example, will tend to overestimate the shoaled wave height of a nonlinear wave, as compared to nonlinear model with similar assumptions (cf., Wei et al, 1995). In cases where slope is not explicitly included in propagation, such as the use of a shoaling coefficient with simple Airy wave theory, the linear models will underestimate shoaling amplification.…”
Section: Hydrodynamic Modelingmentioning
confidence: 99%
“…If vertical variations must be taken into account, these can be separated from the horizontal ones, resulting in a set of shallow water equations for a series of horizontal fluid layers (i.e., multilayer NSW). Recently, non-hydrostatic models, such as Boussinesq models (e.g., [27,30,31]), have increasingly been used in research and damage assessment following major tsunami events.…”
Section: Wave Propagation In Shallow Watersmentioning
confidence: 99%
“…For a proper performance rating, the performance is compared to the results of the FUNWAVE code. FUNWAVE solves the fully-nonlinear Boussinesq equations with finite volume and finite difference methods [30,31]. The flux terms and first-order derivatives are discretized with a fourth-order scheme, while for the higher order derivatives, central difference schemes are used.…”
Section: Performance Considerationsmentioning
confidence: 99%
“…: nonlinearity, a/h, and dispersion, (kh) 2 , are assumed to be of the same order. Although the original Boussinesq approximation accounted only for weak dispersion and nonlinearity, limiting its validity to (very) shallow water, recent advances include full nonlinearity (Wei et al 1995) and high-order dispersion effects (e.g., Madsen et al, 2003), supporting modelling of waves in deep-intermediate water and to very high-nonlinearity (see, e.g., Fuhrman et al, 2004a). Reviews of developments in Boussinesq theory are found in e.g.…”
Section: Nonlinearity In Shallow Watermentioning
confidence: 99%